Cairo Airport Between Origination And Future Vision. Issue 1 (December 2020) - Mahmoud, Mostafa; Rahman, Alaa El Din Abdel; Zakisaeid, Salah
Abstract: Airports are the latest means of transportation that reflect the progress of human civilization and reflect the distinctive identity of each country. The passenger building is the main component of the airport, which in turn contains many dynamic and constantly evolving facilities depending on the increase in passenger traffic and the continued entry of new aircraft and modern operating and service systems that are constantly heading to try to facilitate and accelerate the travel procedures, as the development of airports in recent years is a remarkable development that promotes the level of booms as a result of increased air traffic in the world. The airports have become one of the most important international projects. In this research, Cairo Airport has been chosen because it is considered the largest airport used in Egypt, and the interface that arrives from the outside world to Cairo. It accommodates all foreign air movements for all foreign airlines operating in Egypt. In this research, a detailed explanation about Cairo Airport will be provided by studying its components from the ground side, passenger buildings and the air side, and studying the area of Cairo Airport and how to benefit from unexploited places at the airport by studying the elements of the airport city and how to benefit from the application of the components of the airport city at Cairo International Airport.